What It Takes to Scale Value-Based Industrial Solutions - Frishammar, Johan; Parida, Vinit (MIT Sloan Management Review, 2026)
New research on manufacturers moving to a value-based sales model finds that delivering initial solutions on a one-off basis is relatively straightforward. The challenge lies in scaling those solutions to more customers, which requires structured, repeatable processes and strong, entrenched capabilities. The researchers describe two important phases of capability building that they identified and define the organizational skills, processes, and relationships that successful companies assemble.